Peran Usaha Air Minum Isi Ulang dalam Meningkatkan Perekonomian Masyarakat Kota Padang Panjang Ditinjau dari Perspektif Ekonomi Islam - Riska Aulia; Sandra Dewi (Pusat Riset dan Inovasi Nasional, 2024)
The author's observations show that at Venus Depot, a drinking water refill business, there are frequent employment changes; within two months, two to three employees are replaced, and replacements are often taken by employees from outside the business area. Ini mengakibatkan kontribusi bisnis yang minimal untuk meningkatkan peluang kerja di lingkungan sekitar. Bisnis manajer masih belum memahami konsep sharia. The objective of this study is to determine the role of the Venus Ferill drinking water company in improving the economy of the people of the city of Padang Panjang from an Islamic economic point of view. Research is qualitative with a field approach, and it uses primary and secondary data. It uses data collection, reduction, presentation, and drawing conclusions as data analysis techniques. Menurut hasil penelitian, Venus refill drinking water company in Padang Panjang plays a significant role in providing affordable drinking water, reducing household costs. Affordable drinking water can reduce axpenses and improve a family's financial health. Bisnis penjualan air minum Venus adalah bisnis yang bagus dan halal untuk dikonsumsi. Owner dan karyawan Venus Refill Drinking Water Company bekerja sebagai traders. Dengan bekerja sebagai trader, Anda akan memiliki kemampuan untuk membuat barang yang dapat memenuhi kebutuhan pribadi dan keluarga Anda.